Longitudinal association between cognitive depressive symptoms and D‐dimer levels in patients following acute myocardial infarction. Issue 9 (7th July 2021) - von Känel, Roland; Pazhenkottil, Aju P.; Meister‐Langraf, Rebecca E.; Znoj, Hansjörg; Schmid, Jean‐Paul; Zuccarella‐Hackl, Claudia; Barth, Jürgen; Schnyder, Ulrich; Princip, Mary
Abstract: Background: A prothrombotic tendency could partially explain the poor prognosis of patients with coronary heart disease and depression. We hypothesized that cognitive depressive symptoms are positively associated with the coagulation activation marker D‐dimer throughout the first year after myocardial infarction (MI). Methods: Patients with acute MI (mean age 60 years, 85% men) were investigated at hospital admission ( n  = 190), 3 months ( n  = 154) and 12 months ( n  = 106). Random linear mixed regression models were used to evaluate the relation between cognitive depressive symptoms, assessed with the Beck depression inventory (BDI), and changes in plasma D‐dimer levels. Demographics, cardiac disease severity, medical comorbidity, depression history, medication, health behaviors, and stress hormones were considered for analyses. Results: The prevalence of clinical depressive symptoms (13‐item BDI score ≥ 6) was 13.2% at admission and stable across time. Both continuous ( p  < .05) and categorical ( p  < .010) cognitive depressive symptoms were related to higher D‐dimer levels over time, independent of covariates. Indicating clinical relevance, D‐dimer was 73 ng/ml higher in patients with a BDI score ≥ 6 versus those with a score < 6. There was a cognitive depressive symptom‐by‐cortisol interaction ( p  < .05) with a positive association between cognitive depressive symptoms and D‐dimer when cortisol levels were high ( p  < .010), but not when cortisol levels were low ( p  > .05). Fluctuations (up and down) of cognitive depressive symptoms and D‐dimer from one investigation to the next showed also significant associations ( p  < .05). Conclusions: Cognitive depressive symptoms were independently associated with hypercoagulability in patients up to 1 year after MI. Hypothalamic–pituitary–adrenal axis could potentially modify this effect.